The Effect of Aggressive Tax Practices on Equity Financing Decisions under the Interactive Role of the Profitability Variable: An Applied Study in a Sample of Non-financial Companies Listed in the Iraq Stock Exchange - Babat, maryam Bahaa Al-deen; Hwueish Al-Shujairi , Mohammed (Journal of Economics and Administrative Sciences, 2025)
The purpose of this study is to evaluate and test the relationship between aggressive tax practices and decisions to choose the appropriate financing structure in companies listed on the Iraq Stock Exchange. Aggressive tax policies of a company may have an impact on the specific considerations related to equity issuance as a financing method, and the impact of aggressive tax practices on equity financing decisions in non-financial companies listed on the Iraq Stock Exchange can be formulated as a research problem by examining the relationship between tax practices and equity financing. Both the descriptive inductive approach and the quantitative inductive approach were adopted to extrapolate the prevailing ownership concentration in the research sample companies based on the annual reports of the research sample companies, the quantitative applied approach within the framework of evaluating and analyzing the research variable represented by aggressive tax practices. Finally, the statistical inferential approach was adopted using statistical inferential analysis tools within the framework of testing and analyzing the research hypotheses and determining the results. By influencing corporate funding strategies, shareholder wealth, economic justice, and policy-making to guarantee sustainable business practices and fair tax systems, aggressive tax practices have an impact on equity financing decisions through their interaction with profitability. This study provides novel insights into corporate financial strategies and the implications of tax policy by examining the interactive role of profitability in linking aggressive tax practices to equity financing decisions. The findings indicate that the Aggressive tax practices and equity financing are not related because of different priorities, risks, and incentives.